Watering Stimulation of Alliun cepa L Plants Based on IoT Through the ESP32 Microcontroller and MQTT Protocol - Sirmayanti Sirmayanti (Universitas Medan Area, 2021)
Allium cepa L. (Shallots) is classified as a seasonal plant that requires special water treatment techniques correctly and precise watering methods. Farmers in the highlands of Enrekang Regency, South Sulawesi, mostly still prefer watering this plant traditionally and manually even though it is in large garden areas. Farmers also find it difficult to handle watering crops on large tracts of land and are overwhelmed by not having enough time to care for water evenly. Implementation of Internet of Things (IoT) based onion watering method utilizes an ESP32 microcontroller with the Message Queuing Telemetry Transport (MQTT) protocol, and is very easy for farmers to implement. The MQTT work system implements Publish and Subscribe data. The method and system for designing this tool is that if the shallot plant is 1-10 days old, this tool will water twice a day evenly, the morning and evening. Then if the shallot plant is 11-60 days old, this tool will water only once, in the morning. When the watering automation is implemented, the information system is in the form of a message (on the smartphone) signing by logic 0. Conversely, if this tool does not flush, then the message that comes on the smartphone is as logic 1.